Los procesos de desarrollo en Colombia: una reflexión desde las políticas del Banco Mundial y el papel de las instituciones (2013)
This paper discusses the role of the World Bank and the rule of law in the speech of the redesign of the economy in Latin America and Colombia, the way the questions it has taken the concept and function of the rule of law, and the relationship between an analysis of economic development in the country with which it seeks to show that in the Colombian case especially formal institutions without eliminating the informal, have had major impacts on the current state of the economy Colombian. The answer to the questions clearly be developed based on the different stages of policies and programs proposed by the World Bank between 60-90 decades but, also, for the solution of these questions will depart from a descriptive methodology-qualitative analytical approach for critical findings against each elements